Neural Tube Defects: A case report - Gautam, Bishnu (Journal of College of Medical Sciences-Nepal, 2018)
Neural tube defect is rare congenital defect of fetus. I have a case of 13 weeks period of gestation with meningomeyelocele came for termination of pregnancy. The diagnosis was confirmed by ultrasonography. History suggests that patient had previous neural tube defect baby, non-compliance to folic acid supplements. It is concluded that prenatal counseling, adherence to folic acid supplement and regular follow-up can prevent further complication.